Validation of an Indicator Model (INCODIES) for Assessing Student Digital Competence in Basic Education - Ana García-Valcárcel; Sonia Casillas Martín; Verónica Magdalena Basilotta Gómez-Pablos (Springer, 2020)
Digital competence is a basic skill for citizens and should be systematically assessed, taking into account characteristics such as knowledge, skills and attitudes. However, measuring and identifying the digital competence of students is still a major challenge. To this end, the indicator model (INCODIES) has been developed and validated following the structure of the DIGCOMP model, which can be used to create assessment tests that measure student digital competence when they have completed their compulsory education. This article presents the results of a process of content validation carried out by 77 experts, in both the school and the university context. The analysis of the experts' assessments and the level of agreement among those rating them were carried out following an original method which consists of determining a quantitative index for the validity of content called the Content Validity Ratio (CVR). The results obtained allowed us to confirm that the competences included in the reference framework DIGCOMP are correctly represented in the items formulated for the INCODIES model, which obtained high content validity. The model can serve as a structure and basis for the designing of specific evaluation tests on this topic.